Against All Odds? – National Sentiment and Wagering on European Football - Sebastian Braun; Michael Kvasnicka (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
This paper studies how national sentiment in the form of either a perception or a loyalty bias of bettors may affect pricing patterns on national wagering markets for international sport events. We show theoretically that both biases can be profitably exploited by bookmakers by way of price adjustment (odds shading). The former bias induces bookmakers to shade odds against the domestic team, the latter to adjust them in a way that depends on the demand elasticity of bettors for their national favorite. Analyzing empirically a unique data set of betting quotas from online bookmakers in twelve European countries for qualification games to the UEFA Euro 2008, we find evidence for systematic biases in the pricing of own national teams in the odds for win offered across countries. Variations in the sign and magnitude of these deviations can be explained by differences across countries in the respective strengths of the perception and loyalty biases among domestic bettors.
Keywords: L20; L83; 330; Football; home bias; investment; patriotism; Glücksspiel; Konsumentenverhalten; Fußballsport; Ethnopsychologie; Wahrnehmung; Theorie; Europa